TOOLS FOR ENSURING ECONOMIC SECURITY OF RURAL AREAS DEVELOPMENT - Vitalii BOIKO; Petro OLISHCHUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The theme of this paper is to obtain information on soil fertility characteristics of Chernozem soil to determine the general production capacity of the land for different crop plants. The present state of the complex system of soil properties, relief, climatic conditions, geomorphology, the types of agricultural farming practices and land use, are all contributing to loss of soil fertility with all its negative impacts on the environment. For this purpose, the calculation of Bonitation Note (NB) (soil quality index, bonitation score) is determined on the main agricultural crops according to the natural fertility capacity of the soil. The natural bonitation score is calculated based on the soil characteristics, which is assigned to the coefficients from 0 to 1, depending on the preference given by each characteristic. The studied Chernozem, located in the southeast of the Romanian Plain, more precisely in the Baragan Field, is directly investigated with the environmental factors, which together form homogeneous ecological territory units (UT), these UT having specific advantages at various agricultural uses, such as wheat, corn, sunflower, peas and soybean crops. Following a pedological study, Chernozem is in the second quality class, with 72 points, of the maximum of 100 points. Because this assessment of soil is changing under the influence of natural environmental factors and human intervention, the bonitation score must be permanently updated.